math
posted by Anonymous .
DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y4X) 2.(p1/2Q)2 3.(A+BC)(2X4B) 4.(X1)(X2+2X+3) 5.(A+2B)(3A2+2AB+2B2)

1. 9y^2 + 24yx + 16x^2
Respond to this Question
Similar Questions

algebra
Is this correct? subtract (4a^3+2b^3)(6a^3+5a^2b2ab^2+2b^3) answer: 2a^35a^2b+2ab^2 
math
Using the table (ADBC)= 8 (DACB)=5 (BADC)=3 (BDCA)=1 (DCAB)=2 (it is supposed to be a table but the table won't paste correctly). Deter mine: a) deter mine the winner using the Borda count b) deter mine the winner using the Hare method? 
electrical
when ever a conductor move thought a magnetic field a voltage is in cluded what factors deter mine the amount of voltage that is generated 
electrical
when ever a conductor move thought a magnetic field a voltage is in cluded what factors deter mine the amount of voltage that is generated 
math
Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find a similar equation for (a  b)2. Examine his argument. (a  b)2 = [a + (b)]2 = a2 + 2a(b) + (b)2 = a2 – 2ab + b2 
math
DETER MINE THE PRODUCT OF THE FOLLOWING.1.(3Y+4X)(3Y4X) 2.(p1/2Q)2 3.(A+BC)(2X4B) 4.(X1)(X2+2X+3) 5.(A+2B)(3A2+2AB+2B2) 
English
i need to fix this sentence "Stop or I'll block you!" the boy yelled. I replace block with deter instead because it be stronger word but teacher say that it not tell her anything but that i just read the definition of deter. i not … 
Math
Encircle the error in the following "proof" that the two arbitrary numbers are equal to each other. Let a and b the arbitrary numbers such that a is not equal to b. Then, (a  b)^2 = a^2  2ab + b^2 = b^2  2ab + a^2 (a  b)^2 = (b … 
Polynomials
State whether the following equations are sometimes, always or never true. a) a^22abb^2= (ab)^2, bis not equal to 0 b) a^2+ b^2= (a+b)(a+b) c) a^2b^2= a^22ab+b^2 d) (a=b)^2 = a^2+2ab+b^2 I don't understand what these questions … 
Algebra
1. 10a – 8b () 4a + 5b 2. 5b + 3c () 4b + 3c 3. 6d + 6e () 9d – 8e 4. 8x – 3y () 4x + 8y 5. 6rs – 7bc () 9rs – 7bc 6. 5xy – 9cs ()3xy + cs 7. x2 – 6x + 5 () 3x2– 2x – 2 8. 3y2 – 2y – 1 () 5y2– 2y …